Editorial Vol.1 - Regmi, Prakash Raj (Nepalese Heart Journal, 2000)
Cardiovascular diseases are killer number one in developed countries and are becoming so in the developing countries too. Developing countries like ours are passing through a health transition phase, which is characterised by decrease in epidemic of acute infectious diseases, increase in life expectancy and change in socio-economic structure. Life style changes are already evident in developing countries. The consumption of saturated fats and tobacco is rising in sharp contrast to the overall decline in developed countries. If these patterns of change currently experienced in developing countries follow those experienced previously in the west, an epidemic of cardiovascular diseases is expected in the near future in SAARC nations with its significant impact in the lower Socio-economic class people.